Data Mining Korelasi Penjualan Suku Cadang Sepeda Motor Menggunakan Metode Algoritma Apriori - Asma Ul Husna (Bulletin of Multi-Disciplinary Science and Applied Technology, 2023)
By utilizing customer data that has been stored in a database, management can find out how the current sales system is less efficient, therefore a system is needed to process information data more quickly and precisely in increasing sales of motorbike spare parts by using the Data Mining application. The Apriori Algorithm method works by searching and finding patterns of association between the products being marketed, so that later it can help the company in improving the associated items. And with sales transaction data, companies can know better how they should increase spare parts stock in the company. From the results of testing sales of motorbike spare parts with a total of 219 data, the results of the Apriori Algorithm calculations are: A3 (N-Max) has 23 items, M2 (Yamaha) has 35 items, S1 (Brake Pads) has 15 items.